Clinical manifestations and quality of life in hidradenitis suppurativa patients: survey of participants from an internet support group - Tavora, Isabel Greco [UNESP]; Bissoli, Gabriela Cabral [UNESP]; Miot, Helio Amante [UNESP]; Schmitt, Juliano Vilaverde [UNESP] (Soc Brasileira Dermatologia, 2019)
BACKGROUND: Hidradenitis suppurative is a complex and infrequent autoinflammatory disease that impacts on quality of life. Its pathogenesis is not fully understood, which limits the development of curative treatments. OBJECTIVES: To evaluate clinical and quality of life aspects of hidradenitis suppurativa patients from a social group on the Internet. METHODS: A cross-sectional, Internet-based survey study among participants in a discussion group (Facebook) of individuals with hidradenitis suppurativa. Patients were asked to answer a questionnaire about clinical-demographic aspects and quality of life (DLQI-BRA). RESULTS: A total of 390 individuals agreed to participate in the study, 82% of them female, median age (p25-p75), of 31(25-37) years old, disease onset at 15 (13-23) years, family member affected in 20% of cases, overweight (BMI 29 [25-33]) kg/m2 and severe impact on quality of life (DLQI 20 [13-25]). Regarding Hurley's classification, the participants provided information that enabled classification into: I (19%), II (52%) and III (29%). More severe cases were associated with males (OR = 1.69), higher weight (BMI: OR = 1.03) non-white color (OR = 1.43) and higher frequency of other autoinflammatory diseases (OR = 1.37). STUDY LIMITATIONS: Voluntary adherence survey with self-completion of the questionnaire by 390 from about 1600 group members. CONCLUSIONS: Hidradenitis suppurativa patients who participated in a social network group had onset of the disease after puberty, with a predominance in females and overweight people, with great impact on the quality of life.
Keywords: Suppurative Hidradenitis; Quality of life; Crowdsourcing; Surveys and questionnaires